Answering Jihad : a better way forward - Qureshi, Nabeel (Grand Rapids, Michigan : Zondervan, 2016)
From New York Times bestselling author and former Muslim Nabeel Qureshi comes this personal, challenging, and respectful answer to the many questions surrounding jihad, the rise of ISIS, and Islamic terrorism. San Bernardino was the most lethal terror attack on American soil since 9/11, and it came on the heels of a coordinated assault on Paris. There is no question that innocents were slaughtered in the name of Allah and in the way of jihad, but do the terrorist' actions actually reflect the religion of Islam? The answer to this question is more pressing than ever, as waves of Muslim refugees arrive in the West seeking shelter from the violent ideology of ISIS. Setting aside speculations and competing voices, what really is jihad? How are we to understand jihad in relation to our Muslim neighbors and friends? Why is there such a surge of Islamist terrorism in the world today, and how are we to respond? In Answering Jihad, bestselling author Nabeel Qureshi (Seeking Allah, Finding Jesus) answers these questions from the perspective of a former Muslim who is deeply concerned for both his Muslim family and his American homeland. - Amazon
Keywords: Jihad; Islam; Islam -- Relations -- Christianity; Christianity and other religions -- Islam; Missions to Muslims